Brandteknisk riskvärdering av Tyrs Hov - Clarin,Christoffer; Åkesson,Olof M.; Olsson,Pontus (BTR, 2012)
The following report is an evaluation of the fire safety for Tyrs Hov sports center in Tyringe with emphasis and focus on personal safety in and egress out of the building. The report was produced as part of studying the course Fire Safety Evaluation at the Department of Fire Safety Engineering and Systems Safety at Lund University. Tyrs Hov holds a variety of sporting activities scattered throughout a building holding several floors. Assessment is by means of qualitative and quantitative techniques, where a rough analysis of the relevant fire hazards within the facility is made. From there, a number of fire scenarios are chosen for further analysis, which together cover relevant fire hazards Analysis is done using statistical data, estimates and simulation programs supplemented by hand calculations. The simulation programs used are FDS 5, CFAST 6 and Simulex. Where existing safety systems appear to fail, new suggested measures are implemented to the model, which is then re-analyzed to become subsequently established. The results of the evaluation indicate that the personal safety due to a fire scenario at Tyrs Hov can ́t be regarded as sufficient. If Tyrs Hov would carry through the suggested measures, e.g. the construction of a new fire exit for the bowling alley, the fire safety regarding egress and personal safety in the enclosure chosen for analysis could be considered as adequate.
Keywords: brandscenario; brandteknisk riskvärdering; CFD; effektutveckling; FDS; kritiska förhållanden; personsäkerhet; Tyrs Hov; grovanalys; Simulex; känslighetsanalys; utrymning; utrymningstid.